Studies on sex ratio, condition factor and patterns of phenotypic estimation in stock identification of snow trout, Schizothorax esocinus Heckel, 1838 inhabiting the colder Indian Himalayan region - Akhter, Gulshan; Ahmed, Imtiaz; Ahmad, Mudasir (Journal of Fisheries, 2024)
Schizothorax esocinus, a nutrient-rich food fish offered in Asian countries, is rapidly declining due to severe fishing pressure and pollution in its wild environment, requiring active conservation strategies. Our study examined 196 specimens to elucidate critical biological parameters including sex ratio, length-weight relationships (LWRs), Fulton’s condition factor (K) and morphometric-meristic parameters. The general sex ratio was not substantially departed from the predicted value of 1 : 1, with the exception for the month of May, where χ2 = 4.15 which is greater than the calculated value of 3.84. The correlation between the length and weight was reported as Log W = 0.134209 + 2.5218 log L for males, Log W = 0.19173 + 2.6751 log L for females and Log W = 0.162116 + 2.594 for combined sexes. Schizothorax esocinus demonstrated a negative allometric growth as indicated by the allometric parameter b for the LWR. The two sexes showed no significant differences in morphometric measures. So, this study included combined-sex regression analysis. These comprehensive findings highlight the critical need for conservation efforts in India and neighbouring countries to preserve this valuable fish stock for future generations.